The Potential UV-B Filter of Gel Preparation Containing Ethanol Extract of Bidara Arab Leaf (Ziziphus spina-christi) Cultivated in Indonesia - Mardhiyani, Dini; Aswatul Ulya; Eni Yanti Wulan Desri; Gendis Purno Yudanti; Muslim Suardi; Vonny Kurnia Utama; Kony Putriani; Isna Wardaniati (Universitas Muhammadiyah Surakarta, 2025)
Bidara arab leaf (Ziziphus spina-christi) contains flavonoids, saponins, triterpenoids, alkaloids, steroids, and lipids that may act synergistically as natural UV filters. Flavonoids are highlighted for their ability to absorb UVA and UVB light, while other compounds may enhance photoprotection. Previous studies reported that its ethanol extract contains 1.53% flavonoids and exhibits strong antioxidant activity (LC₅₀ = 90.96 ppm). To formulate gel preparations containing Bidara Arab leaf ethanol extract and evaluate their physicochemical properties, sun protection factor (SPF), and photoprotective efficacy against UV-B–induced erythema. The extract was incorporated into gel at concentrations of 2.5% (F1), 5% (F2), and 10% (F3). Physicochemical tests included organoleptic assessment, pH, viscosity, and spreadability. In vitro SPF was determined using UV-Vis spectrophotometry. In vivo testing involved UV-B–irradiated mice, and erythema was scored to assess protection. All gels met standard parameters (pH 5.34–6.51; viscosity 10.352–15.459 cP; spreadability 5.2–5.8 cm). SPF values were 19.26 (F1), 20.22 (F2), and 20.50 (F3), indicating medium UV-B protection. Erythema scores in all extract-treated groups were 0, with erythema areas of 0.50 mm², 0.38 mm², and 0.19 mm², respectively—significantly lower than in the blank gel (3.96 mm²) and untreated control (7.51 mm²) (p<0.01). Bidara arab leaf extract gel (2.5–10%) shows medium SPF protection and effectively prevents UV-B–induced erythema in mice. These findings support its potential as a natural sunscreen agent.